2010
DOI: 10.1007/s12687-010-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risks and benefits of diagnosing genetic conditions with variable phenotypes through population screening: Klinefelter syndrome as an example

Abstract: Consideration of postnatal population-based genetic screening programs is becoming increasingly common. Assessing the medical and psychosocial impacts of this can be particularly complex for genetic conditions with variable phenotypes, especially when outcomes may be more related to quality of life rather than reducing physical morbidity and mortality. In this article, we present a framework for assessing these impacts, by comparing diagnosis and non-diagnosis at different age points. We use the example of Kli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Herlihy et al [2010Herlihy et al [ , 2011 discussed the medical and psychosocial impacts of postnatal population-based screening for XXY at different ages. The major concern is the currently undiagnosed majority of men with KS does their phenotype differ significantly from the phenotype of the diagnosed men in order to justify the introduction of a screening program?…”
Section: Diagnosing Xxy (Ks)mentioning
confidence: 99%
“…Herlihy et al [2010Herlihy et al [ , 2011 discussed the medical and psychosocial impacts of postnatal population-based screening for XXY at different ages. The major concern is the currently undiagnosed majority of men with KS does their phenotype differ significantly from the phenotype of the diagnosed men in order to justify the introduction of a screening program?…”
Section: Diagnosing Xxy (Ks)mentioning
confidence: 99%
“…In this context the importance of providing parents with accurate information about the frequency of the diagnosis of SCAs and the variability of the outcomes using the best unbiased populationbased follow-up studies on these specific chromosomal abnormalities cannot be over emphasized. One should encourage parents to express their preference for an inclusive or exclusive test as suggested by Herlihy et al [2010] who recommend treating SCAs separately from other abnormal findings and to consider the pros and cons of prenatal detection especially in cases of Klinefelter syndrome.…”
Section: A Dedicated Preconceptional Counseling Sessionmentioning
confidence: 99%
“…Herlihy et al have suggested that the possibility of fertility preservation may tip the scales towards including KS in population based screening, as infertility is the most consistent feature of KS (Herlihy et al 2010). Fullerton et al state that since adolescents are counselled regarding the D. Cutas, K. Hens possibility of sperm banking prior to chemotherapy, adolescents that are diagnosed with KS could be counselled as well.…”
Section: Introductionmentioning
confidence: 99%
“…They note that in adolescents undergoing chemotherapy, it is expected that sperm can be obtained via ejaculation, whereas in KS, a surgical procedure may be required which has only 50 % chances of recovering any sperm (Fullerton et al 2010). As all other features are variable, screening for KS may be premature as the weighing up of risks and benefits is unclear for the moment, and more information is needed before such a program is implemented (Herlihy et al 2010). Furthermore, Herlihy et al acknowledge that including KS in population based screening programmes such as newborn screening would represent a shift away from the traditional goals of such programmes (minimising mortality and severe medical consequences) to ''less tangible outcomes such as decreasing psychological morbidity, preventing less severe medical consequences, and ultimately, towards maximising quality of like (QoL)'' (Herlihy et al 2010: 41)-and they use the example of KS to examine the case for a careful broadening of current screening frameworks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation